Passing the PRINCE2 exams for dummies - Graham, Nick. (Chichester : John Wiley & Sons, 2013)
PRINCE2 is a powerful project management method that helps users plan and control their projects effectively. This guide will help you prepare for and pass the exams, with practical tips on exam strategy and the best ways maximizeise your preparation.
Keywords: PRINCE2 (Computer file); Project management -- Examinations -- Study guides; Project management -- Computer programs